New blood pressure levels in Peruvian high altitude populations and the new North American High Blood Pressure Guidelines - Segura Vega, Luis (2018)
The publication of the new American high blood pressure guidelines, presented by the American Heart Association and the American College of Cardiology, has caused great controversy; some support them for respect and recognition to the scientists who developed the guidelines and others are extremely critical. To higher blood pressure, there is more cardiovascular risk, lower prevalence in the population, and lower distribution between the hypertensive subjects. Any therapeutic proposal to lower blood pressure goals will result in decreasing the cardiovascular risks. For now, we will use the pattern 140/90 mm Hg in our coast and jungle, and its recently determined equivalent 134/89 mm Hg for chronic adult residents of the Andean heights.